Marczewski–Burstin Representations vs. Bernstein and Dense Subsets - Nowik Andrzej (Demonstratio Mathematica, 2016)
We find values of superposition of Marczewski-Burstin operation and operation of finding Bernstein sets. Several counterexamples of Marczewski-Burstin systems are given.